2016
DOI: 10.3390/ijms17111792
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Nanoemulsion Platform of Curcumin Elicit Elevated Apoptosis and Augmentation of Anticancer Efficacy against Breast and Ovarian Carcinomas

Abstract: Vitamin E (VE) tocotrienols (T3), recognized for their cancer-specific anti-proliferative and pro-apoptotic activities, have been previously fabricated into bio-active nanoemulsion (NE) formulations. Here, our viscosity-adapted δ-T3 NE platform was developed to additionally incorporate curcumin (CUR), which is known for its potent suppression of signaling pathways involved in malignant cell growth, survival and metastasis. Thanks to efficient 70:30 wt % surfactant mix of Lutrol F-127:VE-TPGS, in conjunction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The tocotrienol nanoemulsion platform of curcumin can be used to treat breast and ovarian carcinoma. 7 Fatty acid/poly(lactic-co-glycolic acid) NPs used as a drug delivery system enhance the in vitro cytotoxicity and in vivo targeting potential of paclitaxel against ovarian cancer stem cells. 8 addition to others.…”
Section: Routes Of Np Entry Into the Reproductive System Direct Path mentioning
confidence: 99%
“…The tocotrienol nanoemulsion platform of curcumin can be used to treat breast and ovarian carcinoma. 7 Fatty acid/poly(lactic-co-glycolic acid) NPs used as a drug delivery system enhance the in vitro cytotoxicity and in vivo targeting potential of paclitaxel against ovarian cancer stem cells. 8 addition to others.…”
Section: Routes Of Np Entry Into the Reproductive System Direct Path mentioning
confidence: 99%
“…. Wide range of formulations such as polymeric micelles, nanoemulsions and liposomes have been reported to enhance the performance of curcumin both in-vitro and in-vivo, yet the exact mechanism of drug delivery by most of the curcumin-loaded NPs is not fully clear (Steuber et al, 2016;Lin et al, 2012;Pengying et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that gemcitabine-γ-tocotrienol conjugates were least affected by deamination deactivation reaction in vitro when compared with the free and conjugated gemcitabine in solution (Abu-Fayyad and Nazzal 2017). CUR/δ-T3 tocotrienol NEs with average particle size of 261 nm, PDI 0.27 and zeta potential of 35 mV significantly suppressed constitutive NF-κ B activation, and significantly induced apoptosis in breast and ovarian cancer cells, MCF-7 and OVCAR-8 (Steuber et al 2016). Hyaluronic acid-complexed PTX NEs containing DL-α-tocopheryl acetate and soybean oil with a diameter of 85.2±7.55 nm and a zeta potential of -35.7±0.25 mV administered at a dose of 25 mg/kg to nude mice transplanted with CD44-overexpressing non-small cell lung carcinoma cells xenografts suppressed cancer cell growth more than the Taxol and strongly inhibited tumor growth, which could be connected with the specific tumor-targeting affinity of HA for CD44-overexpressed cancer cells (Kim and Park 2017a).…”
Section: Nanoemulsions For Cancer Therapymentioning
confidence: 97%